Actualizing Learning English Grammar Strategy Using New Inventory for University Students - Syafryadin Syafryadin (PAROLE: Journal of Linguistics and Education, 2022)
Learning grammar strategies have been explored by students and teachers. Moreover, research on this issue has been done by several researchers. However, new inventory to measure learning English grammar strategy has been developed and not implemented to identify students’ learning strategy. Thus, the present study aimed to implement and identify the students’ English learning grammar strategy by using new inventory. Besides, this study also wanted to know the challenges of students in implementing those strategies. This study used Mixed method with sequential explanatory.  The participants of this research were 30 students of English Language Department in one of the universities in Bengkulu. The instrument of this study used questionnaire of Grammar Learning Strategy Inventory (GLSI) and the interview guideline.  Those instruments have been validated by two expert judgments and tried out to another class. The quantitative data were analysed by using simple statistic calculation and using percentage for every learning strategy type. However, the qualitative data analysis comprised several steps namely data collection, data condensation, data display, and conclusion. The result shows that students used all strategies in learning grammar, but the dominant one is cognitive strategy, while the least one is social strategy.   The challenges in implementing learning strategy or in learning grammar were poor knowledge of grammar, ineffective time management, less group work, and less sociable because of Covid-19.